Beef Cattle Sustainability Determinants Using Structural Equation Modeling in Pati Regency, Central Java - Agus Setiadi; Aldonny Nurdiansyah; Siwi Gayatri; Siswanto Imam Santoso; Suryani Nurfadillah; Kadhung Prayoga; Joko Mariyono; Limbang Kustiawan Nuswantara (Agriekonomika, 2021)
The research objective was to create a structural model to link social, economic, and environmental variables to the sustainability of the beef cattle business. One hundred twenty beef cattle farmers in Pati Regency were taken as respondents. The exogenous variables studied were social, economic, and environmental factors. Endogenous variables were taken, namely beef cattle sustainability. The model was created using Structural Equation Modeling. The results show that social factors have a positive and significant effect on sustainability, while economic and environmental factors have a negative and significant effect. The net income obtained is low, and the investment return period takes nine years, nine months, and nine days. The number of beef cattle farmers who process dung is only 27.2%. To improve economic and environmental performance, it is necessary to provide training to improve skills in processing feed based on local resources and training in processing livestock manure into fertilizer and biogas.